Export market participation and environmental actions of enterprises in Vietnam. (6th August 2022) - Efobi, Uchenna
Abstract: The outcome of environmental actions from participation in the export market are examined by unpacking some mechanisms that explain the estimated relationship. The empirical strategy utilizes the variation in the distance between the location of the sampled enterprises and the top 25 destinations of Vietnamese exports across sectors, and the weight of each sampled export to total exports in each period, to obtain exogenous variation in the enterprise's export market participation. The result shows a positive relationship between the enterprise's export participation and its overall engagement in environmental actions (such as the sum of its environmental actions, the sum of actions in the investments in equipment towards environmental issues, and total expenditure for the purchase of equipment for environmental actions). Possible mechanisms are international standardization, national certification, and strong enforcement of environmental regulations from export market engagement.